Online impulse buying behavior and marketing optimization guided by entrepreneurial psychology under COVID-19 - Wang, Pei; Chapa, Sindy (Frontiers in Psychology, 2022)
This work aims to promote the development of the online shopping market and improve the online marketing effect of goods. First, entrepreneurial psychology and online shopping are discussed. Then, impulse buying behavior (IBB) is analyzed, and the IBB model and hypotheses of consumers are proposed under the psychological model. Finally, consumers’ IBB during COVID-19 is assessed under the psychological models. Hedonic shopping value is a psychological factor directly affecting consumers’ IBB during COVID-19. The results indicate that COVID-19 has a specific stimulating effect on IBB. Meanwhile, the types of goods consumers buy during COVID-19 vary widely across age groups and regions. Overall, clothing is the most purchased item by consumers. This work provides the main reference for the improvement of the online commodity marketing effect and makes a crucial contribution to the development of the online shopping market.